Ornamental Costus - Skinner, Dave (Ornamental Horticulture, 2016)
In recent years the spiral gingers (genus Costus) have become more and more popular as ornamental garden plants. Dave Skinner describes these plants, including his approach to identification of New World Costus, corrections to some common identification errors, information about cold hardy species, and information about Costus hybrids and cultivars.